Collaborative Governance dalam Implementasi Perda tentang Pengawasan, Pengendalian Peredaran dan Penjualan Minuman Beralkohol di Kabupaten Sukoharjo - Wahyu Nurharjadmo; Ika Nurhayati (Spirit Publik: Jurnal Administrasi Publik, 2022)
Sukoharjo Regency is an area that has been a center for the production of local alcoholic beverages which has been carried out for generations. To overcome the possible impact that is not implemented, the regional government issues a regional regulation that regulates the supervision, control of circulation and sales of alcoholic beverages. In its implementation, the government cannot run alone. In addition to the relevant government agencies, it is necessary to involve parties outside the government through a collaborative governance approach. However, even this process is not easy. Various obstacles can arise for various reasons, considering that there are still many people as producers who depend on this business for their livelihood.